The Influence of Corporate Governance, Intellectual Capital, and Company Size on Financial Performance - Nasrizal, Nasrizal; Mela, Nanda Fito; Falya Zakira Utami (Universitas Bhayangkara Surabaya, 2025)
This study aims to examine the influence of corporate governance, intellectual capital, and company size on financial performance. The dependent variable is financial performance as measured by Net Profit Margin. The independent variables are corporate governance as measured by the size of the board of commissioners, the size of independent commissioners, the size of the audit committee, and intellectual capital as measured by Value Added Intellectual Capital (VAICTM), and company size as measured by total assets. This study uses secondary data from the financial statements of 58 real estate and property companies listed on the IDX in 2019-2023. This study method is purposive sampling and uses multiple linear regression analysis tools. The results of the study are that intellectual capital and company size have a positive influence on financial performance, while the board of commissioners, independent commissioners, and audit committee has no influence on financial performance.